Application Of EVOP Factorial Design Technique For Optimization Of Nisin Production From Lactococcus Lactis (MTCC-440) - PUSPADHWAJA MALL; BIJAY KUMAR MOHANTY; BINITA S. TUNGA; RASHBEHARI TUNGA (International Journal of Pharma and Bio Sciences, 2011)
Evolutionary Operation (EVOP) factorial design technique was sequentially used to optimize concentrations of various media ingredient such as MRS broth, nisin and milk in order to maximize nisin production using Lactococcus lactis (MTCC-440). Traditional method for optimization of media ingredient involves changing one variable at a time and keeping all other parameters constant. However, this method does not determine the interactive effects of different factors. EVOP factorial designing technique was applied consecutively and the results were analyzed statistically and next set of experiments were carried by getting the clue from the previous set of experiments till the effect of individual media components are less than the error limits. Streptococcus agalactiae (NCIM-2401) was used as an indicator strain for quantification of nisin by agar diffusion assay. Nisin yield increased when fermentation was carried out at 30°C at 100 rpm with final formulated media having media-ingredient concentrations MRS broth, milk and nisin 5.5 %, 0.7 % and 0.25 µg/mL respectively. Consequently, with successful implementation of EVOP factorial design technique Nisin production was increased from 206.1 µg/mL to 271.69 µg/mL, which was approximately 1.31 fold.